Pengaruh Ukuran Bukaan Jendela terhadap Pencahayaan Alami pada Perencanaan Ruang Rawat Inap Rumah Sakit Ibu dan Anak di Kota Jambi - Salsabila Putri Prasetyo; Soni Pratomo; Rusydi Sakran; Fetty Febriasti Bahar (Universitas Batanghari Jambi, 2022)
Meeting the needs of light in hospitals can be obtained through natural and artificial lighting. Natural lighting comes from sunlight that enters the room through window openings. Sunlight is believed to have many benefits, especially in terms of health effects. The purpose of this study was to determine the difference in natural lighting obtained from the difference in the size of the openings in the inpatient ward of the Maternal and Child Hospital Design in Jambi City. The research method was carried out through computer simulation with DIALUX Evo 9.1 software by comparing the size of the 2x2m aperture and the 4x2m aperture. The simulation was carried out on September 1, 2021, with average sky conditions at 09.00, 12.00, and 16.00 WIB. The simulation results show that an opening with a size of 4x2m placed in the middle of the wall produces a greater lighting power (397 lux at 09.00, 467 lux at 12.00, and 1707 lux at 16.00) than two openings with a size of 2x2m ( 318 lux at 09.00, 378 lux at 12.00, and 1202 lux at 16.00). From these values, it is shown that the lighting received in the inpatient room is more than adequate following the Standard Regulation of the Minister of Health of the Republic of Indonesia, which is 250 lux. The results of this simulation show that the lighting in the afternoon is greater than in the noon and the morning.